A Novel Power Saving Algorithm for Wireless Sensor Networks - Wang, Hairui; Li, Ya; Wang, Jianying (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Sensor nodes in wireless sensor networks (WSNs) transmit their sensed data to communication module(CM) periodically. Power saving is the most important issues in battery-powered WSNs. In order to prolong the lifetime of the battery, power consumption in each sensor node must be minimum. To achieve this goal, a novel power saving algorithm (NPSA) is proposed in this paper. In the NPSA, packages are transmitted between sensor nodes. It uses a round for sensor nodes to cooperatively transmit data package to CM and drops identified package to reduce power consumption and bandwidth. power-management algorithm is also introduced into the NPSA to enhance the battery lifetime. When finishing package transmitted or dropped, a sensor node will go to suspend until the next round starts. This algorithm is considered efficient that can be implemented in software or hardware. We found that NPSA consumes less power than other algorithms at high node density and low traffic load with multiple CM.